Long-term dietary glutamine supplementation modulates fatty acid profile and health indices in quail meat - Ewa Tomaszewska; Piotr Domaradzki; Kamil Drabik; Kornel Kasperek; Iwona Puzio; Artur Burmańczuk; Justyna Batkowska; Marcin B. Arciszewski; Siemowit Muszyński (Poultry Science, 2025)
This study evaluated the long-term effects of dietary glutamine (Gln) supplementation on the fatty acid (FA) composition of breast meat in Japanese quail. Six-week-old dual-purpose female quails were allocated to four dietary treatments, receiving 0%, 0.5%, 1.0%, or 1.5% Gln from the onset of egg laying until peak production. The experiment was conducted at two time points, after 6 and 12 weeks of Gln supplementation (i.e., at 12 and 18 weeks of age, respectively), to assess age-related changes in lipid metabolism. Fatty acid profiles were determined by gas chromatography, and both relative percentages and absolute contents were assessed. Approximately 37 FA were identified, and Gln supplementation significantly influenced the FA profile, with notable interactions between age and dosage observed for several FAs. In older birds, the total polyunsaturated FA (PUFA) content, particularly n-3 PUFA, decreased, while saturated FA (SFA) levels increased. These shifts resulted in reduced PUFA/SFA, alongside increased atherogenic, thrombogenic, and peroxidation indices. Regarding the main effect of dose, the 0.5% Gln supplementation reduced content of total MUFA and PUFA due to the decrease of C14:1c9, C16:1c9, and C20:3n6, respectively. The 0.5% Gln dose appears to optimize lipid metabolism by improving the n-6/n-3 PUFA balance. The findings indicate that Gln supplementation can modulate lipid metabolism in quails, potentially improving the nutritional quality of the meat by optimizing the balance between beneficial and detrimental FA and providing practical implications for dual-purpose quail production systems. However, the concurrent rise in lipid peroxidation susceptibility warrants further investigation into strategies to maintain meat quality.